ANALISIS GAP TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KESUKSESAN PROJECT (CAPITAL EXPENDITURE) MENGGUNAKAN STANDAR PROJECT MANAGEMENT INSTITUTE (P,I): STUDI PADA PT FAJAR SURYA WISESA, TBK - , Vinsensius Alexander Athe, Dr. Adi Djoko Guritno, MSffi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Fajar Surya Wisesa Tbk. is a company that specializes in paper production, especially for packaging paper. Product characteristic output is B2B (business to business) and already start produce paper since 1987. PT. Fajar Surya Wisesa Tbk is the second largest producer of packaging paper in Indonesia with market share about 30 percent and 93 percent of it for fulfill the domestic demand. On their progress, PT. Fajar Surya Wisesa Tbk keep expand their business with capital expenditure (project). Many projects that already done by PT. Fajar Surya Wisesa Tbk including big project with high budget and can be the pillar for future corporate business improvement. It is necessary to doing project assessment in order to find the weakness in doing project steps. With project assessment and compare it to standard, will raising the gap. Standard that used in research is Project Management Institute (PMI). Based on this research we found that : there are three projects stage and 16 detail execution of projects stage that below the average value. Suggestion for improve has been given for the three projects stage and 16 detail execution of projects stage that below the average value.